Cross‐cultural comparisons between Korean and U.S. adults with respect to texture perception and acceptance of cooked milled rice. (29th April 2018) - Choi, Won Seok; Jarma Arroyo, Sara E.; Seo, Han‐Seok
Summary: This study aimed to determine whether texture perception and acceptance of cooked rice could differ with cultural background, especially between Korean and American participants. Participants evaluated eight cooked rice samples with respect to intensities of textural attributes such as visual stickiness, hardness, stickiness and chewiness. Participants also rated the acceptability of and familiarity with those samples. Results showed that Americans gave higher ratings to cooked rice samples with respect to visual stickiness, stickiness and chewiness, while Koreans gave higher ratings to hardness than their counterpart. For Americans, chewiness was considered as a negative driver; whereas for Koreans, visual stickiness and stickiness were identified as positive drivers of overall liking for cooked rice samples. Moreover, a familiarity level of cooked rice samples was a pronounced positive driver of liking for both American and Korean participants. In conclusion, our findings provide empirical evidence that cultural background influences texture perception and liking of cooked rice. Abstract : It was determined whether texture perception and acceptance of 8 cooked milled rice samples could differ with cultural background, especially between Korean and American participants. For Korean participants, familiarity, visual stickiness, and oral stickiness were identified as positive drivers of overall liking for cooked rice. For American participants, familiarity and chewiness were considered as positive and negative drivers of liking, respectively.